STUDYING OF CORRELATION BETWEEN THE MOLECULAR STRUCTURE AND THE CORROSION INHIBITING EFFECT OF SOME PYRIMIDNE COMPOUNDS - Yousif, Qhatan Adnan (Al-Nahrain Journal of Science, 2018)
Quantum chemical calculations were performed on the pyrimidne and it is derivatives that it useas corrosion inhibitors of iron electrode, using the semi–empirical method AM1. The highestoccupied molecular orbital energy, lowest unoccupied molecular orbital energy, dipole moment andthe total of electronic energies of the molecules is calculated. the assessment of quantum chemicaland corrosion inhibition efficiency studies were carried out to investigate whether any clear linksexist between the results of quantum chemical calculations and inhibition efficiencies experimentalof pyrimidine and it is derivatives by using a linear model encompassing the charge transferresistance " Rt ". Regression equations, with more reliable of correlation coefficients were derivedbetween Rt and the molecular calculations. The significant correlations is evident indicated that thevariation of the corrosion inhibition with the structure of the inhibitors may be explained in terms ofelectronic properties. Keywords: Corrosion,corrosion inhibition,quantum chemical calculations,charge transfer resistance,semi